The renaissance of anti‐neoplastic immunity from tumor cell demise. Issue 1 (13th October 2017) - Ma, Yuting; Pitt, Jonathan M.; Li, Qingqing; Yang, Heng
Summary: Cancer therapies can temporarily reduce tumor burdens by inducing malignant cell death. However, cancer cure is still far from realization because tumors often gain resistance to current treatment and eventually relapse. Accumulating evidence suggests that successful cancer interventions require anti‐tumor immunity. Therapy‐induced cell stress responses ultimately result in one or more cell death modalities, including apoptosis, autophagy, necroptosis, and pyroptosis. These irreversible dying processes are accompanied by active or passive release of cell death‐associated molecular patterns (CDAMPs), which can be sensed by corresponding pattern recognition receptors (PRR) on tumor‐infiltrating immune cells. This crosstalk with the immune system can reawaken immune surveillance in the tumor microenvironment (TME). This review focuses on immune‐modulatory properties of anti‐cancer regimens and CDAMP‐mediated communications between cell stress responses and the immune contexture of TME. In addition, we describe how immunogenic cell death can elicit strong and durable anti‐tumor immune responses.